A resorbable scaffold for bone replacement - Paola Andrea Bustamante; Maria Carolina Anessi (Brazilian Journal of Radiation Sciences)
All tissue banking activities are depending on tissue donors. The donor rate is still low in Argentina, and the tissue demanding is still not fulfilled. For this reason, tissue engineering has become a necessary discipline to be investigated. Our project is conducted to obtain a 3D resorbable printed scaffold seeded with mesenchymal stem cell (MSC), to conduct real bone. We produced three polylactic acid (PLA) filaments with different loads of hydroxyapatite (HA): 3%, 5% and 10%. The mixtures were homogenous and the three filaments were suitable for 3D printing and were used to print 3D scaffolds samples. The scaffolds were irradiated with range doses of 15 kGy to 25 kGy for sterilization purposes and to evaluate if the degradation polymer rate is regulated with the irradiation dose. The elaborated filaments were optimally printable. In addition they turned out to be not cytotoxic (cell viability greater than 70%) and whit good cellular adherence. In this way, our biomaterial seems to be good for scaffolds for bone replacement.